A young Dutchman views post-Civil War America : diary of Claude August Crommelin - Crommelin, Claude August, 1840-1874 (Indiana University Press, 2011)
Not long after the end of the American Civil War, a wealthy young Dutchman by the name of Claude August Crommelin embarked on a tour of the young country, visiting New England, the Middle Atlantic States, the Upper Mississippi Valley, and the war-ravaged South. His family connections allowed him to meet important people, and his interests in industry, politics, and public institutions led him to observe what others might not have noticed. His meticulously kept journal reveals an inquisitive traveler with.